2018
DOI: 10.1002/pssb.201800377
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Interfacial Interaction and Its Influence on the Electronic and Optical Properties of Two‐Dimensional WS2/TX2CO2 (TX = Ti, Zr) van der Waals Heterostructures

Abstract: Two‐dimensional (2D) transition metal dichalcogenides (TMDs), carbides (MXenes), and their heterostructures showcase several key properties that can address emerging energy needs, in particular for solar energy conversion and storage devices. Understanding the fundamental science of these heterostructures is paramount to designing them with desirable properties. Using a detailed theoretical study of 2D WS2/TX2CO2 (TX = Ti, Zr) van der Waals heterostructure, as a typical case, based on density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Hexagon is the basic building block of the crystal structures for most 2D materials, from graphene to 2D transition‐metal dichalcogenides and others . Recently, pentagon has been confirmed, by both experimental and theoretical studies, to be another basic building block for constructing novel 2D sheets, as shown in Figure .…”
Section: Introductionmentioning
confidence: 97%
“…Hexagon is the basic building block of the crystal structures for most 2D materials, from graphene to 2D transition‐metal dichalcogenides and others . Recently, pentagon has been confirmed, by both experimental and theoretical studies, to be another basic building block for constructing novel 2D sheets, as shown in Figure .…”
Section: Introductionmentioning
confidence: 97%